Randomised comparison of provisional side branch stenting versus a two-stent strategy for treatment of true coronary bifurcation lesions involving a large side branch: the Nordic-Baltic Bifurcation Study IV. Issue 1 (19th January 2020) - Kumsars, Indulis; Holm, Niels Ramsing; Niemelä, Matti; Erglis, Andrejs; Kervinen, Kari; Christiansen, Evald Høj; Maeng, Michael; Dombrovskis, Andis; Abraitis, Vytautas; Kibarskis, Aleksandras; Trovik, Thor; Latkovskis, Gustavs; et al.
Abstract : Background: It is still uncertain whether coronary bifurcations with lesions involving a large side branch (SB) should be treated by stenting the main vessel and provisional stenting of the SB (simple) or by routine two-stent techniques (complex). We aimed to compare clinical outcome after treatment of lesions in large bifurcations by simple or complex stent implantation. Methods: The study was a randomised, superiority trial. Enrolment required a SB≥2.75 mm, ≥50% diameter stenosis in both vessels, and allowed SB lesion length up to 15 mm. The primary endpoint was a composite of cardiac death, non-procedural myocardial infarction and target lesion revascularisation at 6 months. Two-year clinical follow-up was included in this primary reporting due to lower than expected event rates. Results: A total of 450 patients were assigned to simple stenting (n=221) or complex stenting (n=229) in 14 Nordic and Baltic centres. Two-year follow-up was available in 218 (98.6%) and 228 (99.5%) patients, respectively. The primary endpoint of major adverse cardiac events (MACE) at 6 months was 5.5% vs 2.2% (risk differences 3.2%, 95% CI −0.2 to 6.8, p=0.07) and at 2 years 12.9% vs 8.4% (HR 0.63, 95% CI 0.35 to 1.13, p=0.12) after simple versus complex treatment. In the subgroup treated by newer generation drug-eluting stents, MACE was 12.0% vs 5.6% (HR 0.45, 95% CI 0.17 to 1.17, p=0.10) after simple versus complex treatment. Conclusion: In the treatment of bifurcation lesions involving a large SB with ostial stenosis, routine two-stent techniques did not improve outcome significantly compared with treatment by the simpler main vessel stenting technique after 2 years. Trial registration number: NCT01496638 .